PENGARUH BOBOT LAHIR DENGAN PENAMPILAN ANAK BABI SAMPAI DISAPIH - Nangoy, Marfiane M.; Lapian, M. T.; Najoan, M.; Soputan, J. E. M. (Universitas Sam Ratulangi, 2015)
THE EFFECT OF BIRTH WEIGHT WITH THE APPEARANCE OF THE PIGLETS UNTIL WEANING. The purpose of this research is to determine the corellation of birth weight with the appearance of the piglets until weaning. This research used the method of observation. Results or data obtained in this research, piglets from each parent is divided into 3 categories: high, medium, low. Retrieval of data held on a new born piglets, piglets aged 1 week until the time of weaning. Parameters observed in this research is the birth weight of piglets per head, body weight gain, the weight of piglets, and mortality (MRTA) piglets before weaned (%). Data were analyzed and presented descriptively, which is describing and explaining the general picture of direct observation. Based on the results of this research we concluded that litter size piglets, determines how high the birth weight, weaning weight, body weight gain, and mortality. The greater the birth weight more likely to obtain a high weaning weight as in this research the highest birth weight is 1.64 kg after weaning reached 7.54 kg. Keywords: Birth Weight, Piglets, Weaning